Cloning and expression of prolactin gene in laying pigeon - ZHANG, MIN; ZHANG, AI-TING; ZHU, SHA; LIU, LIAN-LONG; ZOU, X T (The Indian Journal of Animal Sciences, 2012)
In order to understand the phylogenetic diversity and expression character of prolactin (PRL) molecule, the cDNA of PRL was isolated and cloned from female American silver king pigeon (Columbia livia) pituitary gland by a degenerate primer and nested reverse transcription polymerase chain reaction (RT-PCR) based strategy. The expected expression of mRNA in different tissues and status was quantified by real-time quantitative PCR (FQ-PCR). The cloned cDNA contains 658bp nucleotides, encoded 219 amino acids and deduced amino acid sequences showed high similarities and identity with the corresponding sequences of chicken, budgerigar, India pealfowl, comb duck, duck, goose, turkey, ring-necked pheasant, Java sparrow, ostrich, ring-necked pheasant and quail. PRL was widely expressed in tissues analyzed, and highest level of PRL mRNA expression was observed in the pitutary whereas the lowest in the kidney. Comparable high level of PRL mRNA expression was observed in oviduct and ovary. PRL mRNA expression increased significantly in incubation, compared to laying.